IN VITRO SHOOT TIP CULTURE OF BANANA CULTIVAR MEITEI HEI - LALRINSANGA, ROBERT; H.VANLALDIKI; W.I MEITEI (The Bioscan, 2013)
Micropopagation is preferred over the conventional method of propagation in banana owing to its faster multiplication rate, uniformity in planting materials, production of disease-free planting materials, higher bunch weight, more fingers and hands and less variability in fruit size and shape. The apical meristem or shoot-tip culture is very efficient for rapid clonal micropopagation. Though abundant information on the micropropagation of banana is available for cultivars in India and abroad, there is only little or no information on micropropagation of Meitei Hei, a popular local variety of Manipur. Thus, study was undertaken during 2009-10 in the Tissue Culture Laboratory of the Department of Horticulture, CAU, Imphal on the in vitro shoot tip culture of Meiteti Hei banana to analyze its micropropagation potential. Results revealed that the highest multiple shoot induction was found in MS+5mg1-1BAP at 2.17 shoots while MS+1 mg1-1NAA+0.2 mg1-1BAP gave the longest regenerated shoots after 45 days of incubation. Highest number of roots was found in MS+2 mg1-1NAA. 98-100% survival was found in all the ex-vitro hardening media of sand, soil:FYM (2:1) and soil:vermicompost (2:1).